Diversity of Trichoderma species isolated from soil - Syd Abdul Rahman, Sharifah Siti Maryam; Abd Aziz, Nor Azwady; Mohd Zainudin, Nur Ain Izzati (Department of Biology, Faculty of Science, Universiti Putra Malaysia, 2016)
Soils consist of complex mixtures of mineral, water, air, organic matter and as an ecosystem of a large number of countless microorganisms such as bacteria, fungi and nematodes. Due to the limitation on understanding of fungi biodiversity in soil, many people do not know there consists of very useful microbe that can help in suppression of plant pathogens. Trichoderma (Hypocreales, Ascomycota) is one of the microorganisms that living in all types of soil. Trichoderma species has been used as a biological control agent of phytopathogens due to its abundance and having an antagonistic property. This study will provide checklists of Trichoderma species that have been isolated from cultivated crop soils in Malaysia. The objectives of this study are to isolate and identify Trichoderma species from soil based on morphological characterization and to calculate diversity of Trichoderma species based on Shannon-Wiener Index. Soil samples from each cultivated agricultural crops were collected in three spots in 17 locations around Malaysia. Isolation of Trichoderma was completed using soil dilution technique to obtain a pure single colony-forming unit (CFU). A total of 253 of Trichoderma isolates were successfully isolated from rhizosphere of different crops. All isolates were tentatively identified into six species such as T. harzianum (114 isolates), T. asperellum (65 isolates), T. hamatum (22 isolates), T. viride (26 isolates),T. koningii (20 isolates) and T. virens (6 isolates).The differences between species were characterized based on their colony features, pigmentation on potato dextrose agar (PDA) and the branching of conidiophores. The diversity index of Trichoderma species found in the Malaysia soil was 1.43 and T. harzianum was dominated. Due to diverse species of Trichoderma found in Malaysia, it will increase the opportunity in selection for biological control agent of plant diseases.